1969
DOI: 10.1152/jappl.1969.27.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flow on transpulmonary circulatory transport functions.

Abstract: Lung transport functions (distributions of circulatory transit times across the lung) were characterized in four anesthetized dogs at various levels of mean pulmonary blood flow. The central circulation was found to approximate a mathematically linear, time-invariant system when respiratory frequencies were maintained at 40/min or more. Lung transport functions were obtained from 144 pairs of lung-input and lung-output dilution curves using a lumped-parameter model and an iterative convolution technique. Avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

1975
1975
1990
1990

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 14 publications
2
35
0
1
Order By: Relevance
“…Similarity has been demonstrated for transorgan transport functions in the kidney by Gomez et al, 22 in the lung over a very limited range of alveolar and left atrial pressures by Knopp and Bassingthwaighte,23 and in the coronary bed by Knopp et al 17 Data from the latter study are plotted in Fig. 11, showing a fair degree of similarity.…”
Section: Tests For Similarity Of Washout Curves At Different Flowssupporting
confidence: 69%
See 1 more Smart Citation
“…Similarity has been demonstrated for transorgan transport functions in the kidney by Gomez et al, 22 in the lung over a very limited range of alveolar and left atrial pressures by Knopp and Bassingthwaighte,23 and in the coronary bed by Knopp et al 17 Data from the latter study are plotted in Fig. 11, showing a fair degree of similarity.…”
Section: Tests For Similarity Of Washout Curves At Different Flowssupporting
confidence: 69%
“…For the concentration-time curves, recalling that h(t) = F · C(t)/m i , (equation 2), then: (22) and for the constant volume system: (23) Equations 22 and 23 show that for a system with stable dispersive properties, a change in F doesn't affect the peak heights of C(t) but does change the spread of the curve, the areas being inversely related to F. Similarly, C(t D2 ) = C(t D1 ) and C(t E2 ) = C(t E1 ) while t D2 = F 1 t D1 /F 2 and t E2 = F 1 t E1 /F 2 . This may be viewed merely as normalization of the time scale of t/t.…”
Section: Tests For Similarity Of Washout Curves At Different Flowsmentioning
confidence: 99%
“…Recording the transport function, Bassingthwaighte (1966) observed in normal human legs that the indicator dispersion was proportional to the mean transit time over a sixfold change of flow rates, suggesting that the rate of spatial longitudinal spreading of indicator with distance travelled is primarily a function of the geometry of the vascular systems, not of the rate of flow. In the pulmonary vascular bed where multiple parallel pathways and different regional perfusion rates may exist, it was shown that average relative dispersion was about twice (0.46) that found for segments of arteries (0.23), and that the relative lispersion tended to increase as the mean transit time increased, suggesting that the vascular geometry may alter with alteration in the perfusion in such a circulatory bed of heterogeneous perfusion (Knopp and Bassingthwaighte 1969). The dependency of the relative dispersion on the perfusion pressure and flow is more dominant in the coronary circulatory bed as shown in this study.…”
Section: Discussionmentioning
confidence: 94%
“…It seems that the determination of transit time must be useful only when it is related to the indicator dispersion, because the latter may be determined mainly by the distance travelled by the dye particles injected (Bassingthwaighte and Warner 1965). Furthermore, the transport function may change with changing blood flow rate as was found in pulmonary circulation by Knopp and Bassingthwaighte (1969).…”
mentioning
confidence: 94%
“…When a circulatory system is involved, it is called circulatory transport function (Bassingthwaighte 1970), that is the probability density function of transit times through the system. Since extensive studies of Bassingthwaighte and co-investigators (Bassingthwaighte 1966;Coulam et al 1966;Bassingthwaighte et al 1966;Bassingthwaighte and Ackerman 1967;Knopp and Bssingthwaighte 1969), the physiological meaning of transport function is being clarified; the ratio of the mean transit time to the standard deviation of transport function (called relative dispersion) is constant for a simply perfused system such as aorta and branching arteries even with the flow changing by 6 times (Bassingthwaighte 1966), but it is variable in a more complicated-structured system (Knopp and Bassingthwaighte 1969), so that in pulmonary circulatory bed, it varied with increased flow suggesting that an alteration in perfusion homogeneity has occurred. Knowledge of the path-length distribution seems very important for the clinical purpose in coronary circulation, in particular in the assessment of the development of collateral circulation, for under such conditions the path-length distribution may be altered (Liedtke et al 1973).…”
mentioning
confidence: 99%